Long-run impacts of the conflict in Ukraine on grain imports and prices in Africa - Lacina Balma; Tobias Heidland; Sebastian Jävervall; Hendrik Mahlkow; Adamon N. Mukasa; Andinet Woldemichael (African Development Review, 2024)
Russia's invasion of Ukraine has threatened global grain supplies as it reduces production and exports while increasing trade costs. While the overall share of Africa's trade with Ukraine and Russia is small, the concentration of imports in products such as wheat, other grains, and fertilizer is critical to food security. This paper investigates the long-term impacts of the conflict on grain imports and prices in Africa. We use a long-run general equilibrium trade model to study three scenarios that may evolve as a consequence of the conflict: (1) a heavily reduced Ukrainian production of wheat and other grains; (2) rising trade costs with Ukraine and Russia due to disrupted trade routes in the Black Sea and the sanctions against trading with Russia; and (3) an outright ban on Russian grain export. The model simulations show that the conflict severely affects grain imports, raising local prices for wheat and other grains, with especially strong effects in high import-dependent countries. That creates risks for food security in some African countries.
Keywords: 330; agriculture; food insecurity; food prices; grain; trade; trade disruptions; war; wheat